The complete chloroplast genome of the Euphorbia maculata L. (Euphorbiaceae): characterization and phylogeny - Wang, Yiheng (Mitochondrial DNA B Resour, 2020)
Euphorbia maculata is an important medicinal plants of the family Euphorbiaceae. The complete chloroplast genome reported here is 162,685 bp in length, including two inverted repeats (IRs) of 26,822 bp, which are separated by a large single-copy (LSC) and a small single-copy (SSC) of 90,514 bp and 18,527 bp, respectively. The whole chloroplast genome of E. maculata contains 111 genes, including 77 protein-coding genes, 4 transfer RNA, and 30 ribosome RNA. Phylogenetic analysis indicated that E. maculata is closely related to E. milii and E. tirucalli.